Maternal iron deficiency assessed by serum ferritin and birth outcomes in mainland China - Hang Zhou; Yiming Lu; Jianying Luo; Binyu Pan; Qihua Zhao; Min Chen; Zheng Feei Ma (Scientific Reports)
Abstract Iron deficiency is prevalent among pregnant women because of the increased maternal iron requirements. Uncorrected maternal iron deficiency can lead to adverse neurodevelopmental outcomes in neonates. Therefore, the aim of this study was to assess serum ferritin concentration and prevalence of iron deficiency among pregnant women in Jiangsu, China. Within a cohort study, pregnant women were followed up from 2nd trimester of pregnancy until their labour. They were assessed for iron status in 2nd and 3rd trimesters using serum ferritin. In addition, neonatal APGAR score and birth weight were assessed in order to determine if maternal iron deficiency was associated with these neonatal outcomes. A total of 1688 pregnant women were followed up until their labour. The mean age of participants was 29 ± 4 years and 54.0% of them were multigravidas. Mean serum ferritin concentration in 2nd trimester was significantly higher than 3rd trimester (59.9 vs. 22.2 ng/mL) (P < 0.001). The prevalence of iron deficiency using serum ferritin concentration cut-off of < 15 ng/mL in 2nd and 3rd trimesters was 11.9% and 37.4%, respectively (P < 0.05). Maternal iron deficiency as assessed by serum ferritin concentration in 2nd and 3rd trimesters of pregnancy was not associated with neonatal outcomes (all P > 0.05). Our study reported that increased prevalence of maternal iron deficiency in 3rd trimester, suggesting that screening and supplementation of at-risk pregnancies can be used as a preventive strategy to tackle the issue. Consideration should be given to ensure adequate maternal iron status through pregnancy.